Gold(i)-catalyzed C-glycosylation of glycosyl ortho-alkynylbenzoates: the role of the moisture sequestered by molecular sieves. Issue 82 (22nd September 2016) - Chen, Xiaoping; Wang, Qiaoling; Yu, Biao
Abstract : C-Glycosylation of glycosyl ortho -hexynylbenzoates with allyltrimethylsilane or silyl enol ethers could proceed smoothly under the catalysis of Ph3 PAuNTf2, wherein the moisture sequestered by the molecular sieves ensured the gold(i )-catalytic cycle. Abstract : C-Glycosylation of glycosyl ortho -hexynylbenzoates with allyltrimethylsilane or silyl enol ethers could proceed smoothly under the catalysis of Ph3 PAuNTf2 to provide the corresponding C-glycosides in high yields and stereoselectivity, wherein the moisture sequestered by the molecular sieves was disclosed to play a critical role in the gold(i )-catalytic cycle.